On the dynamics of crown structure in simultaneous two droplets impact onto stationary and moving liquid film. (31st January 2015) - Raman, K.A.; Jaiman, R.K.; Lee, T.S.; Low, H.T.
Abstract: We present a numerical study on the dynamic behaviour of two droplets impinging simultaneously onto a liquid film. A high density ratio based lattice Boltzmann method is employed for the present two-phase computations. Formation of a central uprising jet is observed due to the collision and coalescence of in between rims caused by the impacting droplets. Effect of separation gap between the droplets, film thickness, viscosity and gas density on the crown structure and jet behaviour are systematically studied. The influence of a moving wall with a liquid film on the jet behaviour is further investigated. It is shown that for a larger separation gap between the droplets, a delay in formation of central jet is observed while the spread length increases. For the thin films, the central jet height increases with the increase in film thickness, however a reversal in this behaviour is observed for the thicker films. The rate of increase of jet height and spread length is found to decrease with increase in gas density. Effect of wall velocity is found to enhance the upstream jet, while it suppresses the central and the downstream jets.